Distance monitoring vision system for automobiles using image processing - Lijauco, Marc Carlo (Animo Repository, 2012)
The thesis aims to create a vision system for vehicles that would prevent frontal collisions. The system is more of an aid to the driver, giving notifications whenever there is a possibility of collision. With the use of a camera, this system is able to get series of images that would undergo processes of detection and distance calculations. And by utilizing OpenCV, detection of vehicles through Haar and distance measurement by perspective warping have been possible. Critical distances relative to the current speed of the system's vehicle is the point of comparison that would result to proper notification of Green LED, Red Led or Red LED + buzzer. The Pn-board Diagnostic 2 terminal of newer vehicles enables input of speed to the system. And overall, the processes happen in an embedded system (Blackfin ADSP 537) that allows stand-alone operation, thus creating a system that works while on the road.